Aeolian stratigraphy describes ice-age paleoenvironments in unglaciated Arctic Alaska. (15th February 2018) - Gaglioti, Benjamin V.; Mann, Daniel H.; Groves, Pamela; Kunz, Michael L.; Farquharson, Louise M.; Reanier, Richard E.; Jones, Benjamin M.; Wooller, Matthew J.
Abstract: Terrestrial paleoenvironmental records with high dating resolution extending into the last ice age are rare from the western Arctic. Such records can test the synchronicity and extent of ice-age climatic events and define how Arctic landscapes respond to rapid climate changes. Here we describe the stratigraphy and sedimentology of a yedoma deposit in Arctic Alaska (the Carter Section) dating to between 37, 000 and 9000 calibrated radiocarbon years BP (37–9 ka) and containing detailed records of loess and sand-sheet sedimentation, soil development, carbon storage, and permafrost dynamics. Alternation between sand-sheet and loess deposition provides a proxy for the extent and activity of the Ikpikpuk Sand Sea (ISS), a large dune field located immediately upwind. Warm, moist interstadial times (ca. 37, 36.3–32.5, and 15–13 ka) triggered floodplain aggradation, permafrost thaw, reduced loess deposition, increased vegetation cover, and rapid soil development accompanied by enhanced carbon storage. During the Last Glacial Maximum (LGM, ca. 28–18 ka), rapid loess deposition took place on a landscape where vegetation was sparse and non-woody. The most intense aeolian activity occurred after the LGM between ca. 18 and 15 ka when sand sheets fringing the ISS expanded over the site, possibly in response to increasingly droughty conditions as summers warmed and active layers deepened. With the exception of this lagged LGM response, the record of aeolian activity at the Carter Section correlates with other paleoenvironmental records from unglaciated Siberia and Alaska. Overall, rapid shifts in geomorphology, soils, vegetation, and permafrost portray an ice-age landscape where, in contrast to the Holocene, environmental change was chronic and dominated by aeolian processes. Highlights: Yedoma stratigraphy downwind of Arctic sand sea is a proxy for dune-field activity. Reduced aeolian activity and soil development occurred during interstadials. Most active aeolian activity occurred after the LGM. Aeolian sand and loess deposition dictated environmental change in ice-age Arctic Alaska.